Challenging the prevailing paradigm of displacement and resettlement risks, impoverishment, legacies, solutions (2018 Routledge)
Development-caused forced displacement and resettlement (DFDR) is a critical problem on the international development agenda. The frequency of forced displacements is rapidly increasing, the sheer numbers of uprooted and impoverished people reveal fast accelerating trends, whilst government reporting remains poor and misleading. Challenging the Prevailing Paradigm of Displacement and Resettlement analyzes widespread impoverishment outcomes,​risks to human rights, and other adverse impacts of displacement; it documents under-compensation of expropriated people, critiques cost externalization on resettlers, and points a laser light on the absence of protective, robust, and binding legal frameworks in the overwhelming majority of developing countries.
Includes bibliographical references and index.
Keywords: Forced migration